A Decentralized Method Using Artificial Moments for Multi-Robot Path-Planning. (10th January 2013) - Xu, Wang-bao; Chen, Xue-bo; Zhao, Jie; Huang, Tian-yun
For the local path-planning of multi-robots, a decentralized method is presented where each robot plans its own path in the following steps for each iteration. Firstly, an optimal way representative point ( OWRpoint ) is obtained for guiding the robot to move along a shorter path. Then, the robot moves a step under the control of its own motion controller, which is designed based on artificial moments. In the motion controller, attractive and repulsive moments are used to move robots closer to their OWRpoints and away from obstacles, while coordinated moments are used to resolve the conflicts between robots. Two simulations are given to test the method and the results indicate that the method is valuable as it meets the requirements of the real-time property while optimizing the performance measure of each robot: namely, the path travelled to reach the robot's target.